Catalogue and Bibliography of the Hong Kong Carabidae Latreille, 1802 (Coleoptera: Adephaga), with notes on the historic boundaries of Hong Kong as related to zoological collections - Aston, Paul (Zootaxa, 2016)
A complete list of Carabidae species historically collected in Hong Kong combined with more recent records and notes on their biology is given. Notes on the historic boundaries of Hong Kong through the colonial period are given, as this is an important element relating to our understanding of the origins of historic zoological collections made in the region. Likewise a list of collectors in Hong Kong up to the outbreak of hostilities in the Second World War is given. A full bibliography of Hong Kong Carabidae is included.